O19.3 Pills, pleasure and privacy: early experiences of pre-exposure prophylaxis among men in the vicprep study. (13th September 2015) - Murphy, DA; de Wit, JBF; Lal, L; Audsley, JM; Roth, N; Moore, R; Tee, BK; Read, T; Wright, E
Abstract : Background: There has been limited research on the lived experience of taking antiretrovirals as HIV pre-exposure prophylaxis (PrEP). We explored men's experiences as participants in Australia's first PrEP demonstration project. Methods: After attending clinic visits, participants completed a self-report online survey on behaviour, attitudes and experiences. This paper analyses responses to the first (i.e. 3-month) survey on: 1) pill taking (including adherence and interruptions); 2) sex since starting PrEP; and 3) disclosing PrEP use. Responses to items on experiences of PrEP were measured on a 5-point scale (1 = strongly disagree, 5 = strongly agree). Results: At 31 March 2015, 76 participants had completed a 3-month survey; all gay/bisexual men (mean age 37.7 years). Forty-one men (53.9%) reported missing any PrEP doses. The median number of doses missed was 1 (mean 2.04). Missing doses was most commonly attributed to forgetting. Six men reported interrupting PrEP for 2 days or more. Side-effects (usually mild) were reported by 34 men (44.7%). Participants strongly agreed that PrEP had reduced their worries about HIV acquisition (mean 4.53; SD 0.77); they agreed that they were open with sexual partners about PrEP (mean 4.20; SD 1.2), and agreed that PrEP made them feel more confident about sex (mean 4.17; SD 0.98). Participants moderately agreed that they were careful to whom they disclosed (mean 3.36; SD = 1.4). However they disagreed that they had experienced negative reactions (mean 1.99; SD 1.14), and disagreed that potential sex partners would avoid them (mean 2.03; SD 1.01) Conclusion: These findings are notable because they support the results of recent qualitative research on the role of PrEP in decreasing anxiety around HIV. Caution around disclosure (including to sexual partners) suggests concern about negative reactions (despite few actual occurrences) and underscores the current novelty of PrEP as a prevention strategy. Disclosure of interest statement: The VicPrEP study was funded by the Victorian Department of Health and study drug was supplied by Gilead. Dean Murphy receives funding from the Australian Government Department of Health and a research grant from the Victorian Department of Health.